1995
DOI: 10.1073/pnas.92.17.7882
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of herpes simplex virus 1 origin-binding protein with DNA polymerase alpha.

Abstract: The herpes simplex virus 1 (HSV-1) genome encodes seven polypeptides that are required for its replication. These include a heterodimeric DNA polymerase, a singlestrand-DNA-binding protein, a heterotrimeric helicase/primase, and a protein (UL9 protein) that binds specifically to an HSV-1 origin of replication (oris). We demonstrate here that UL9 protein interacts specifically with the 180-kDa catalytic subunit of the cellular DNA polymerase a-primase. This interaction can be detected by immunoprecipitation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Moreover, cdk-2-mediated phosphorylation of proteins that regulate DNA replication, such as HsCdc6, is also required for cellular DNA replication (40). Finally, the expression of many enzymes required for cellular DNA replication (including DNA ligase 1 and DNA Pol ␣) is dependent on cdk-2 activity (18,52), and, as noted above, some of these cellular proteins may also be required for HSV DNA synthesis (27,46,50,75).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cdk-2-mediated phosphorylation of proteins that regulate DNA replication, such as HsCdc6, is also required for cellular DNA replication (40). Finally, the expression of many enzymes required for cellular DNA replication (including DNA ligase 1 and DNA Pol ␣) is dependent on cdk-2 activity (18,52), and, as noted above, some of these cellular proteins may also be required for HSV DNA synthesis (27,46,50,75).…”
Section: Discussionmentioning
confidence: 99%
“…Of these proteins, DNA ligase 1 may serve to circularize the viral genome, an event required for viral DNA synthesis (5). Cellular DNA Pol ␣ interacts with, and is activated by, the HSV origin binding protein (50). Topoisomerase II (p170) has been reported to be involved in viral DNA replication, since inhibition of this cellular enzyme results in some inhibition of HSV DNA synthesis (27).…”
Section: Discussionmentioning
confidence: 99%
“…Two other observations, however, provide support for the possible involvement of pol ␣. First, Lehman and co-workers (51) demonstrated that UL9, the HSV-1 origin-binding protein, interacts with pol ␣, thus providing a potential mechanism to recruit pol ␣ to initiation sites. Second, immunofluorescence studies indicate that herpes replication compartments contain pol ␣ (52).…”
Section: Discussionmentioning
confidence: 99%
“…The key role for AR in diabetic cataractogenesis is further supported by studies in AR-overexpressing mice. Sugar cataracts form in transgenic diabetic mice expressing human AR in the lens, but not in wild-type streptozotocin-induced diabetic mice which have very low expression of AR (Varma and Kinoshita, 1974; Lee et al, 1995). AR siRNA transfection and inhibition suppressed high glucose-induced ROS formation, NF-kappaB activation, and apoptosis in rat lens epithelial cells (Nambu et al, 2008).…”
Section: Aldose Reductase and Other Complications In Diabetesmentioning
confidence: 99%